Long noncoding RNA small nucleolar RNA host gene 12/microRNA-138-5p/nuclear factor I/B regulates neuronal apoptosis, inflammatory response, and oxidative stress in Parkinson’s disease - Lei Yan (Taylor & Francis Group, 2021)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that causes tremors, gait rigidity, and hypokinesia. We determined the effects of long noncoding RNA small nucleolar RNA host gene 12 (lncRNA SNHG12) on the development of PD. StarBase analysis and dual-luciferase reporter assay verified the interaction between lncRNA SNHG12 and microRNA-138-5p (miR-138-5p). The effects of suppressed lncRNA SNHG12 and increased miR-138-5p levels on mRNA were determined using quantitative real-time-PCR (qRT-PCR) in 1-methyl-4-phenylpyridinium (MPP+) treated SH-SY5Y cells. Increased lactate dehydrogenase (LDH) activity, apoptosis, cleaved-Caspase3/Caspase3 ratio, inflammatory response, reactive oxygen species (ROS) level, decreased cell viability, and superoxide dismutase (SOD) activity were observed in MPP+-stimulated SH-SY5Y cells. Transfection of the lncRNA SNHG12-plasmid reduced neuronal apoptosis, inflammation, and oxidative stress in MPP+-stimulated SH-SY5Y cells that were rescued by adding the miR-138-5p mimic. These results showed that lncRNA SNHG12 could affect neuronal apoptosis, inflammation, and oxidative stress in a PD cell model by regulating miR-138-5p expression. TargetScan and dual-luciferase reporter analysis suggested that miR-138-5p targeted nuclear factor I/B (NFIB). Furthermore, the expression level of NFIB was downregulated after MPP+ stimulation in SH-SY5Y cells. After transfecting with the miR-138-5p inhibitor, NFIB-siRNA, and co-transfecting and detecting NFIB mRNA and protein, we found that miR-138-5p negatively regulated NFIB expression. In conclusion, lncRNA SNHG12 could alleviate neuronal apoptosis, inflammation, and oxidative stress in a PD cell model by regulating the miR-138-5p/NFIB axis, providing new therapeutic targets for patients with PD.